Expression of TLR2 and TLR4 in lesions of patients with tegumentary american leishmaniasis - Tuon, Felipe Francisco; Fernandes, Elaine Ribeiro; Duarte, Maria Irma Seixas; Amato, Valdir Sabbaga (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
OBJECTIVES: The aim of this study was to describe the pattern of expression of Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) in skin biopsies of patients with American tegumentary leishmaniasis (ATL) caused by Leishmania braziliensis. METHODS: This prospective study evaluated 12 patients with ATL caused by Leishmania braziliensis confirmed by polymerase chain reaction. Immunohistochemistry was performed to determine the expression of TLR2 and TLR4. The number of NK cells, dendritic cells and macrophages in the tissue were calculated. The cytokine expression was determined using the anti-TNF-α, anti-IFN-Γ, anti-IL-1 and anti-IL-6. Double immunostaining reactions were used to determine the cell expressing TLR2 and TLR4. RESULTS: The numbers of cells expressing TLR2 and TLR4 were 145.48 ± 82.46 cell/mm² and 3.26 ± 4.11 cell/mm² respectively (p < 0.05). There was no correlation of TLR2 and TLR4 with the amount of cytokines and the number of NK cells, dendritic cells or macrophages. The double immunostaining revealed that TLR2 was expressed by macrophages. CONCLUSION: In human cutaneous leishmaniasis caused by Leishmania braziliensis, TLR2 is the most common TLR expressed during active disease, mainly by macrophages although without correlation with the amount of cytokines and number of cells.